Spastic dystonia in stroke subjects: prevalence and features of the neglected phenomenon of the upper motor neuron syndrome. Issue 4 (April 2019) - Trompetto, Carlo; Currà, Antonio; Puce, Luca; Mori, Laura; Serrati, Carlo; Fattapposta, Francesco; Abbruzzese, Giovanni; Marinelli, Lucio
Highlights: 74% of stroke subjects was affected by spastic dystonia in their hypertonic wrist flexor muscles. Only a minority of stroke subjects was affected by spasticity in their hypertonic wrist flexor muscles. Evaluation of EMG activity during static muscle stretch is pivotal to assess spastic dystonia. Abstract: Objective: Spastic dystonia is one of the positive phenomena of the upper motor neuron syndrome (UMNS). It is characterised by the inability to relax a muscle leading to a spontaneous, although stretch-sensitive, tonic contraction. Although spastic dystonia is a recognized cause of muscle hypertonia, its prevalence among hypertonic muscles of stroke subjects has never been investigated. Differently from spasticity, which is an exaggerated stretch reflex, spastic dystonia is viewed as an efferent phenomenon, due to an abnormal central drive to motoneurons. Methods: In 23 hemiparetic stroke subjects showing increased muscle tone of wrist flexors, surface EMG was used to investigate the presence of spontaneous, stretch-sensitive EMG activity in flexor carpi radialis . Results: Spontaneous, stretch-sensitive EMG activity was found in 17 subjects. In the remaining 6 subjects, no spontaneous EMG activity was found. Conclusions: The majority of stroke subjects is affected by spastic dystonia in their hypertonic wrist flexor muscles. Only a minority of subjects is affected by spasticity. Significance: To stop spastic dystonia from being the neglected aspect of UMNS, it is essential to link its definition to increased muscle tone, as occurred for spasticity. Recognizing the real phenomena underling muscle hypertonia could improve its management.